PENILAIAN KINERJA GURU MENGGUNAKAN METODE TOPSIS - Kurnia, Yogi _ (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2018)
Determining the level of individual contributions in completing the tasks for which they are responsible needs to be carried out objectively, transparently and through a specific method that can be trusted for accuracy. In addition to teaching in the classroom, a teacher is required to have the character as implied by Tut Wuri Handayani. The problem of the teacher performance appraisal process occurs because of unclear criteria and assessment weight. Decision Supprot System (DSS) can help the optimal decision-making process, namely TOPSIS (Technique For Order Preference by Similarity to Ideal Solution). In determining teacher performance appraisal agreed upon criteria for assessment of teacher performance assessment criteria: Pedagodic Competence (K1), Personality Competence (K2), Social Competence (K3), Proffesional Competence (K4). The acquisition of the final result of the TOPSIS calculation becomes the Teacher Performance Assessment Decision with the Status: Poor, Good, and Very Good. Very good teacher performance assessment, namely